Transformation of the Meaning of Zakat, Infaq and Sadaqah: Contextualisation of the Quranic Semantic Approach - Nugraha, Babang Prima; Wanto, Sugeng (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
This study examines the concepts of zakat, infaq, and shadaqah (ZIS) in the Qur'ān through Toshihiko Izutsu’s semantic approach and Syed Muhammad Naquib al-Attas’s Islamic worldview paradigm. Unlike previous research focusing solely on lexical meanings, this study aims to address the gap in understanding how ZIS functions beyond mere terminology, as practical instruments for spiritual purification, social welfare, and economic justice within the Islamic value system. Motivated by the global challenges of sustainable development and social inequality, the research explores how Islamic charitable concepts can contribute to contemporary development goals. The primary objective is to trace the semantic transformation of these terms from their pre-Qur’ānic roots to their post-Qur’ānic developments, and to interpret their actualization as spiritual, social, and economic instruments aligned with key sustainable development priorities.This study employs a qualitative-descriptive method with textual content analysis of classical Qur’anic exegesis, Arabic lexicography, and relevant global development documents. Findings reveal that zakat signifies purification and growth, infaq represents conscious and value-driven expenditure, and shadaqah reflects sincerity and spiritual truthfulness. Together, these concepts contribute to poverty alleviation, promotion of social justice, and strengthening of community cohesion.The integration of semantic and Islamic worldview approaches demonstrates that ZIS is not merely a financial obligation but an integral component of the Islamic epistemic framework, uniting linguistic, spiritual, and sociological dimensions. This study affirms the relevance of ZIS as an instrument for sustainable development and offers a novel methodological contribution to Islamic studies that is both contextual and transformative.